Basel Implementation in Banking in Indonesia - Wayuningsih, Nining; Fatmawati, Putri Noviah; Sudrajat, Anton; Wiradinata, Rochanda (Journal of Social Science and Business Studies, 2024)
This study’s goal is to determine the application of Basel in banking in Indonesia. Bank Indonesia in issuing banking regulations refers to the Bank for International Settlement (BIS) policies related to liquidity, especially as a reference to protect Indonesian banks from crises caused by insufficient liquidity needs in the Bank. policies from the BIS will be accommodated first by the Islamic Financial Service Board (IFSB). IFSB is used as a reference for regulators to make banking policies. One of the IFSB committees, namely the Basel committee in the field of banking supervision, has issued provisions that are a reference for international banking, namely Basel 1, Basel II and Basel III. This study collects data using a descriptive qualitative methodology and secondary data obtained from literature studies. The results of the research show that banks in Indonesia have implemented regulations according to the Basel III international standard OJK has adopted Basel recommendations and has implemented Basel 1, 2 and 3 although there are some shortcomings but the application of risk management is more effective and efficient. The application of the continuation of Basel III is adjusted to the conditions of national banking proportionally.